Dasar psikologis dan pedagogis pendidikan - bilillah, dian sarah (Maliki Interdisciplinary Journal, 2025)
Education is the main foundation and important process in teaching and learning activities to shape the character and competence of quality students. Its achievement requires a deep understanding of the psychological and pedagogical basis of education. The psychological basis in education is closely related to the understanding of how psychological aspects such as cognitive development, motivation, and individual behavior affect the learning process. Psychological theories such as behaviorism, cognitivism, humanism and psychoanalysis are references in designing effective and flexible learning strategies for the needs of students. Meanwhile, the pedagogical basis of education emphasizes the importance of a systematic approach in guiding and directing children or students towards maturity. Pedagogy itself includes theories and practices that combine human values, morals, and teaching process strategies that are adjusted to the socio-cultural and psychological conditions of students. In its application, an educator is required to have the competence to create a meaningful and inclusive learning process. And the educational process can produce individuals who are not only academically intelligent, but also emotionally and socially.